Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan RM Bebek Sinjay Ketengan, Bangkalan - Muhammad Hilman Wadied; Mudji Kuswinarno (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
RM Bebek Sinjay Ketengan, Bangkalan is one of the most famous culinary destinations in Bangkalan Regency. This business is already popular among the people of Indonesia. One of the characteristics of this culinary is the sambal pencit (Indonesian chili paste with young and raw mango slices). As one of the well-known businesses, RM Bebek Sinjay Ketengan, Bangkalan must have good employee performance. Starting from the work discipline possessed by employees, and the work motivation needed by employees. This study aims to determine and analyze the influence of discipline and work motivation on the performance of employees at RM Bebek Sinjay Ketengan, Bangkalan. The purpose of this study was to determine the effect of discipline and work motivation on employee performance at RM Bebek Sinjay Ketengan, Bangkalan both in partial and simultaneously. This study used a quantitative method with a survey method. The respondents were 90 employees of RM Bebek Sinjay Ketengan, Bangkalan. Thus, this research is categorized as population research. The data were gathered through interviews, questionnaires, and a literature study. The analysis technique used was the Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, and Hypothesis Test. The results of the study were (1) work discipline partially (individually) had a positive and significant effect on the performance of employees of RM Bebek Sinjay Ketengan, Bangkalan of 0.772 with a t-count of 7.190 -table of 1.66660, with a significant level of 0.000 0.05, and with a beta value of 0.576. (2) work motivation has a partial (individual) positive and significant effect on the performance of the employees of RM Bebek Sinjay Ketengan, Bangkalan of 0.360 with a t-count of 4.747 t-table of 1.66660, with a significant level of 0.000 0.05, and with a beta value of 0.380. (3) Discipline and work motivation simultaneously influence the performance of the employees of RM Bebek Sinjay Ketengan, Bangkalan with an f-count of 249.773 f-table of 3.10 and with a significant level of 0.000 0.05.Keywords: Discipline, Employee Work Motivation and Performance